IMPLEMENTASI PEMBELAJARAN AL-QUR’AN DENGAN METODE AL-HIKMAH DI MI KHADIJAH MALANG - Sumbulatin Mi’atu Habbah; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Learning is a process where changing behavior for the sake of experience. Experience can be obtained through the learning process. It takes experience to become knowledge. Likewise with the knowledge of the Qur'an obtained in the same way. Reading also memorizing the Qur'an is part of the knowledge of the Qur'an, which is obtained by learning. Thus, one of the materials in Islamic education that is important to learn is the material to read the Qur'an. Therefore researchers interested in reviewing MI MI Khadijah Malang is the only Islamic educational institution in Malang that uses a new method, the Al-Hikmah method in learning the Qur'an. The type of research used is descriptive qualitative research. In this study the data collection techniques used were observation, in-depth interviews and documentation. While the data analysis used is the theory of Miles and Hubermen, namely data reduction, data presentation and conclusion conclusions. This study also checks the validity of the data by extending participation, perseverance monitoring, and triangulation of sources and techniques. The results of the Al-hikmah research method are: (1) the application of the Al-Hikmah learning method: (a) the Al-hikmah learning method uses classical techniques of reading, listening, pure classical, accent, direct method and repetition. (2) Learning Outcomes of the Al-Hikmah Method: (a) Assessment of structured learning ranging from daily, monthly and yearly (b) Completing volumes 1 to volumes of tajwid takes 3 to 4 years. (3) Weaknesses and Strengths of the Al-Hikmah method: Weaknesses: (a) Requires a professional Qur'an teacher. (B) It takes a long time about 4 years to pass the volume. Strengths: (a) Has structured material. (B) Material books become the main capital in learning (c) Adequate time allocation (d) Using direct methods and repetition Key Word: Metode Al-Hikmah, Al-Qur’an learning